Islamic Banking Users Are Hunger For Service Quality - Nuradli Ridzwan Shah Mohd Dali (Islami Bank Training Research Academy, 2024)
Islamic banking is growing tremendously since its inception in the past three decades. The products and services offered by the Islamic banking industry either in its assets or liability sides are competitive with the products and services of the conventional banking. The growth of the Islamic banking in tandem with the conventional banking give alternative to the consumers, thus comparison between these two systems could be made by the consumers in selecting their banking providers. Therefore, this study is conducted to analyze the factors influencing banking preferences of Islamic Banking and Conventional users using factor analysis and logistic regression. Result shows that there are three factors contribute to the banking selection preferences for Islamic banking and conventional banking users. In conclusion, the Islamic banking users are looking forward for a better service quality since this factor is significant negative compared to the service quality from the conventional banking.